Methylation of hypoxia-inducible factor (HIF)-1α by G9a/GLP inhibits HIF-1 transcriptional activity and cell migration. Issue 13 (31st May 2018) - Bao, Lei; Chen, Yan; Lai, Hsien-Tsung; Wu, Shwu-Yuan; Wang, Jennifer E; Hatanpaa, Kimmo J; Raisanen, Jack M; Fontenot, Miles; Lega, Bradley; Chiang, Cheng-Ming; Semenza, Gregg L; Wang, Yingfei; et al.
Abstract: Hypoxia-inducible factor 1 (HIF-1) is a master transcriptional regulator in response to hypoxia and its transcriptional activity is crucial for cancer cell mobility. Here we present evidence for a novel epigenetic mechanism that regulates HIF-1 transcriptional activity and HIF-1-dependent migration of glioblastoma cells. The lysine methyltransferases G9a and GLP directly bound to the α subunit of HIF-1 (HIF-1α) and catalyzed mono- and di-methylation of HIF-1α at lysine (K) 674 in vitro and in vivo . K674 methylation suppressed HIF-1 transcriptional activity and expression of its downstream target genes PTGS1, NDNF, SLC6A3, and Linc01132 in human glioblastoma U251MG cells. Inhibition of HIF-1 by K674 methylation is due to reduced HIF-1α transactivation domain function but not increased HIF-1α protein degradation or impaired binding of HIF-1 to hypoxia response elements. K674 methylation significantly decreased HIF-1-dependent migration of U251MG cells under hypoxia. Importantly, we found that G9a was downregulated by hypoxia in glioblastoma, which was inversely correlated with PTGS1 expression and survival of patients with glioblastoma. Therefore, our findings uncover a hypoxia-induced negative feedback mechanism that maintains high activity of HIF-1 and cell mobility in human glioblastoma.